Perancangan Sekolah Internasional Pekanbaru Dengan Pendekatan Eko Arsitektur - Irawan, Jerry Dwi; Aldy, Pedia; Rijal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
As one of the developing cities, Pekanbaru has been done international relations with other countries in economical, social, and political sectors. It also affects the education sector, and therefore it needs the proper tools to facilitate educational activities in Pekanbaru city. The international school is an educational facility that implements an international curriculum in the teaching system, also has been recognized internationally as well as produces Certified International graduates. This international school has applied the principles of eco-architecture with purpose keeping the designed building has more synergy, considering the environment condition. However, in aiming more in specific concept, it applies the concept of “Holistic” which is the combination of the design criteria of ecological design. Holistic in ecological design is aimed at the principles as follows: (1) energy saving; (2) sensitive to climate; (3) eco-friendly. This International School fulfills all the criteria that appropriate with the curriculum also facilities of educational standards and infrastructure nationally as well as the implementation of the concept that is used to create an international school which refers to ecological architecture.Keywords: Pekanbaru as a developing city, Educational Facility, International School, Eco-architecture, Holistic.